Market Orientation, Creativity, and Use of Digital Technology on the Performance of Technology Start-ups in Jakarta - Fitria Madaniah Prasetyo; Mahnun Mas'adi; Riski Baroroh; Fatari Fatari; Cikita Berlian Hakim (Westscience Press, 2025)
This study examines the effects of market orientation, creativity, and the use of digital technology on the performance of technology start-ups in Jakarta. A quantitative research design was employed using a structured questionnaire distributed to 250 founders and managers of technology start-ups. All variables were measured using a five-point Likert scale, and data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) version 25. The results of multiple linear regression analysis indicate that market orientation (β = 0.312, p < 0.001), creativity (β = 0.274, p < 0.001), and the use of digital technology (β = 0.356, p < 0.001) each have a positive and significant effect on start-up performance. Furthermore, the simultaneous analysis shows that these three variables collectively explain 55.6% of the variance in start-up performance (R² = 0.556). The findings highlight that digital technology usage is the strongest predictor of performance, followed by market orientation and creativity. This study contributes to the literature by providing empirical evidence from an emerging economy context and offers practical insights for start-up founders and policymakers to enhance performance through strategic market orientation, creative capabilities, and effective digital technology utilization.